Effect of storage duration on the Type and concentration of aflatoxin in local paddy and polished rice. (Baghdad Science Journal, 2004)
?Natural Occurrence of aflatoxin Bi and B2 was investigated monthly in paddy rice stored for duration of six months. Aflatoxin B| was detected at the beginning of storage. The concentration of aflatoxin Bi in paddy and polished rice was found to be (0.3 and ()) ppb respectively while aflatoxin B2 W'as not detected in both paddy and polished rice afler six months of storage, concentration of aflatoxin Bi ‘ ’ ' reached 3 ppb in paddy rice and 0.9 ppb in polished rice, while the study proved that the concentration of aflatoxin in paddy rice was higher than polished rice as a result of processing which reduce the toxin